2015
DOI: 10.14527/pegegog.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural education in Turkey: An analysis of 1st-5th grades curriculum objectives

Abstract: The aim of this study is to evaluate 1st-5th grades curriculum objectives with regards to multicultural education principles in Turkey. To achieve this goal, document analysis of qualitative method was used. The curriculum standards of compulsory courses were examined by using Castagno's (2009) framework that offers six approaches for multicultural education. According to the results of this study, the total number of 2.44% objectives has been found related to multicultural education principles. There are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
2
7
0
8
Order By: Relevance
“…Seban and Uyanık (2016), Keskin and Yaman (2014) found the proportion of multicultural education in Social Studies course to all attainments as 13%, and Cırık (2008) found it as 17,20%.…”
Section: Discussionmentioning
confidence: 99%
“…Seban and Uyanık (2016), Keskin and Yaman (2014) found the proportion of multicultural education in Social Studies course to all attainments as 13%, and Cırık (2008) found it as 17,20%.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been observed that the research in the international field is at a stage in which the practices and the experience related to this process are examined in line with the prevalence of multicultural education practices (Baltes, Hernandez & Collins, 2015;Golub, 2014;Guth, McAuliffe & Michalak, 2014;Perveen, 2014). Studies conducted on multiculturality in Turkey generally show that teacher candidates, teachers, administrators and academics are positive in multiculturality and multicultural education (Akkaya, Kırmızı & İşçi, 2018;Alanay & Aydın, 2016;Avcı & Faiz, 2018;Başarır, Sarı & Çetin, 2014;Damgacı & Aydın, 2013;Kahraman & Sezer, 2017;Polat, 2012), although there are many deficiencies in curricula and textbooks (Akar & Keyvanoğlu, 2016;Akhan & Yalçın, 2016;Çayır, 2016;Keskin & Yaman, 2014;Seban & Uyanık, 2016). Therefore, education policies in Turkey are still not equipped to bring multiculturality into educational environments (Köşker & Özgen, 2018).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Alanyazındaki çalışmalarda, İngilizce ders kitaplarında çokkültürlülük öğelerinin göz ardı edildiği ve ağırlıklı olarak hedef kültüre yer verildiği belirtilmiştir. Bununla beraber, kaynak kültür, hedef kültür ve bunların dışında kalan uluslararası kültürel öğelere aynı oranda yer verilmesi gerektiği de belirtilmektedir (Çelik ve Erbay, 2013;Demirbaş, 2013;Erdoğan, 2015;Seban ve Uyanık, 2016;Üzülmez ve Karakuş, 2018;Zorba ve Çakır, 2019). İncelenen kitaplarda kaynak kültüre ilişkin öğelere (yabancı yazarlı ders kitaplarında olduğu gibi), hedef kültüre ilişkin öğelere oranla daha az yer verilmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…In Turkey, English coursebooks mostly include cultural aspects of the target language and quite a few elements referring multiculturalism (Bulut and Arıkan, 2015;Çakır, 2010;Çelik and Erbay, 2013;Demirbaş, 2013;Erdoğan, 2015;Seban and Uyanık, 2016;Üzülmez and Karakuş, 2018). In order to overcome this deficiency mentioned in the literature, the English curriculum and English textbooks were revised in parallel with the Common European Framework of Reference for Languages (CEFR) and the European Language Portfolio (ELP) between 2011 and 2018 by the Ministry of National Education.…”
Section: Purpose and Significancementioning
confidence: 99%